Kepemimpinan Kepala Sekolah Dalam Menguatkan Etos Kerja Guru SDN Aengdake II Kecamatan Bluto Kabupaten Sumenep - Haliyah Haliyah; Ashari Ashari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
In this study using a qualitative research method by descriptive approach with data collection techniques of observation, interviews and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and verification or drawing conclusions. While the research subjects were school principals and teachers. While the research location was carried out at SDN Aengdake II, Bluto District, Sumenep Regency.The results showed that the school principal at SDN Aengdake II, Bluto District, Sumenep Regency had a significant role in strengthening the teacher's work ethic. The principal uses a leadership model with a system of openness and democracy. adopt a collaborative approach by establishing open communication, providing ongoing support, and empowering teachers to participate in decision-making.